Características pós abate de novilhos terminados com grão de aveia branca e/ou casca do grão de soja - Mayer, Andrei Retamoso (2013)
The aim of this study was to evaluate the effect of oat grain in relation to soybean hulls and mixtures thereof, as an energy source, the components are not part and carcass characteristics and meat quality of feedlot steers. We used 36 castrated male cattle, originated from the crossing between Charolais x Nellore, age and average final weight of 356.4 kg and 24 months, respectively. The animals were distributed in treatments, as the energy source in the concentrate fraction of the diet with oat grain, soybean hulls or mixture of oat grain and soybean hulls (1:1). The experimental design was a randomized block design with three treatments and 12 experimental units per treatment, each animal an experimental unit. With respect to fat accumulation renal, inguinal, and ruminal set of total fat, there was a significant effect (P <0.05), and the amount of fat and total renal treatments mixture of animal and soybean hulls top the oat. For the other components are not part of the carcass showed no difference between the different energy sources (P> 0.05). As for the effects of energy sources on the quantitative characteristics of the carcass, only differ with regard to the conformation (P <0.05). Since the housing steers the treatments of soybean hulls and oat were carcasses regular conformation and secondly mixing carcasses showed good conformation. The amount of fat was higher in carcasses of animals fed soybean hulls and mixing with respect to oat (P <0.05), there was an inverse relationship to muscle/fat. Regarding the cooling time of housing in the region Longissimus dorsi muscle during periods of 0, 12 and 24 hours there was no significant difference between the pH and temperature (P> 0.05). The pH of the muscle Recto femoralis, animals fed with a mixture of soybean hulls and oat (1:1) showed a lower pH at the time that the carcasses were placed (0 hour) and withdrawals (24 hours) camera cold (P <0.05). No significant values were checked for color, texture, marbling, thawing loss and cooking, organoleptic characteristics and shear force of beef from steers fed different energy sources (P> 0.05). The soybean hulls as the oat mixture between these and do not alter the main characteristics of the carcass and meat, so with different energy sources can be used in the diet of cattle, which benefit producer and refrigerator.